Analisis Efektivitas Penerapan Mobile Application di PT. Kereta Api Indonesia (Persero) - Benny Agustian; Deni Nurdyana Hadimin (Prodi S1 Administrasi Bisnis Universitas Sangga Buana YPKP, 2022)
A company will try to improve the quality of service for the community. A company that has developed several innovations PT. Kereta Api Indonesia (Persero) by creating the KAI Access mobile application, which is an application that is used to buy tickets online without having to queue at the station counter. Therefore, the purpose of this research is to determine the effectiveness of the application of the KAI Access mobile application at PT. Kereta Api Indonesia (Persero) which refers to four evaluation variables, namely information quality, service quality, usage, and user satisfaction. This research is qualitative descriptive research that aims to determine the quality of information, service quality, usage, and user satisfaction without making a comparison or linking with other variables. The data used in this research are interviews with key informants from PT. Kereta Api Indonesia (Persero), interviews with five users of the KAI Access application, and a questionnaire were conducted with a total of 42 respondents as supporting data for this research. The results showed the effectiveness of the application of the KAI Access mobile application at PT. Kereta Api Indonesia (Persero) can be said to be very effective. This can be seen from the research results of each evaluation variable, namely the quality of information that is accurate, relevant, and complete, the quality of service that is responsive and empathetic, easy use for daily use, and efficient, effective, and satisfied user satisfaction. Keywords: Effectiveness, Mobile Application KAI Access